2012
DOI: 10.1002/app.36758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing and functionalization methods on nylon‐6,6 nanocomposites with Helical‐ribbon carbon nanofibers

Abstract: Helical‐ribbon carbon nanofiber‐based nylon‐6,6 nanocomposites were obtained by three processing methods: in situ polymerization, solvent processing through coagulation, and melt compounding. Composites were produced with pristine carbon nanofibers and four functionalization treatments, HNO3, O3, air/NH3, and ethylenediamine, which form sets of two liquid/gas phase treatments and two acidic/basic treatments. Dispersion was monitored at the microscale by optical microscopy, showing clear differences depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Therefore modification and reinforcement of PA66 have drawn much attention to improve its physical properties and to introduce new properties. For example, Rodriguez-Pastor et al [12] reported the preparation of helical-ribbon carbon nanofiber-based nylon-6,6 composites by three processing methods and the effect of CNTs modification methods on the properties of composites. Krause et al [13] investigated the influence of CNTs production method and aspect ratio on percolation threshold of melt-mixed PA66.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore modification and reinforcement of PA66 have drawn much attention to improve its physical properties and to introduce new properties. For example, Rodriguez-Pastor et al [12] reported the preparation of helical-ribbon carbon nanofiber-based nylon-6,6 composites by three processing methods and the effect of CNTs modification methods on the properties of composites. Krause et al [13] investigated the influence of CNTs production method and aspect ratio on percolation threshold of melt-mixed PA66.…”
Section: Introductionmentioning
confidence: 99%
“…In carbon nanoparticles, the mean particle size of the detected agglomerates is around 0.9 μm 2 51 . Well dispersed fillers in a nanocomposite displayed a homogeneous particle distribution through the whole matrix rather than some large agglomerate in a specific area 52 . The composite with 0.5 wt% of MoS 2 showed mostly small agglomerates (smaller than 5 μm) that are well dispersed through the matrix, and the same tendency is observed by increasing the filler concentration to 1.0 wt%, although some larger agglomerates are further observed.…”
Section: Resultsmentioning
confidence: 98%